Sound-Evoked Responses in the Vestibulo-Ocular Reflex Pathways of Rats - Chen, Tianwen; Huang, Jun; Yu, Yue; Tang, Xuehui; Zhang, Chunming; Xu, Youguo; Arteaga, Alberto; Allison, Jerome; Mustain, William; Donald, Matthew C.; Rappai, Tracy; Zhang, Michael; et al. (Frontiers in Neuroscience, 2021)
Vestibular evoked myogenic potentials (VEMP) have been used to assess otolith function in clinics worldwide. However, there are accumulating evidence suggesting that the clinically used sound stimuli activate not only the otolith afferents, but also the canal afferents, indicating canal contributions to the VEMPs. To better understand the neural mechanisms underlying the VEMPs and develop discriminative VEMP protocols, we further examined sound-evoked responses of the vestibular nucleus neurons and the abducens neurons, which have the interneurons and motoneurons of the vestibulo-ocular reflex (VOR) pathways. Air-conducted clicks (50–80 dB SL re ABR threshold, 0.1 ms duration) or tone bursts (60–80 dB SL, 125–4,000 Hz, 8 ms plateau, 1 ms rise/fall) were delivered to the ears of Sprague-Dawley or Long-Evans rats. Among 425 vestibular nucleus neurons recorded in anesthetized rats and 18 abducens neurons recorded in awake rats, sound activated 35.9% of the vestibular neurons that increased discharge rates for ipsilateral head rotation (Type I neuron), 15.7% of the vestibular neurons that increased discharge rates for contralateral head rotation (Type II neuron), 57.2% of the vestibular neurons that did not change discharge rates during head rotation (non-canal neuron), and 38.9% of the abducens neurons. Sound sensitive vestibular nucleus neurons and abducens neurons exhibited characteristic tuning curves that reflected convergence of canal and otolith inputs in the VOR pathways. Tone bursts also evoked well-defined eye movements that increased with tone intensity and duration and exhibited peak frequency of ∼1,500 Hz. For the left eye, tone bursts evoked upward/rightward eye movements for ipsilateral stimulation, and downward/leftward eye movements for contralateral stimulation. These results demonstrate that sound stimulation results in activation of the canal and otolith VOR pathways that can be measured by eye tracking devices to develop discriminative tests of vestibular function in animal models and in humans.